Improving Family Medicine Residents’ Written Communication - Francois, José (Revue canadienne de l’éducation médicale, 2012)
Background: Although competency in written communication is a core skill, written communication is seldom the focus of formal instruction in medical education. The objective of this intervention was to implement a self-assessment strategy to assist learners in improving their letter writing skills and then to evaluate its feasibility, reliability and potential educational value. Methods: Eight first-year family medicine residents from two teaching sites completing a six month family medicine rotation used a self-assessment process which included a self-study module and an assessment tool for letters. Each resident applied the self-assessment tool to eight to ten consecutive consult/referral request letters. Participants submitted initial and redrafted letters for independent rating. Results: Analysis of the content, style and global ratings of the initial 77 draft letters showed multiple deficiencies in the content of their letters. It was confirmed that by using the self-assessment tool, residents were able to reliably assess the quality of their letters. Residents’ assessments and those of the expert closely correlated (Pearson correlation 0.861, p < 0.0001). Over the course of the study the residents’ overall performance improved and the difference in total scores between the initial drafts and the rewritten letters narrowed. Conclusion: A self-assessment process of written communication significantly improves the quality and completeness of routine consult/referral request letters. <span style="line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-CA; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">